1987
DOI: 10.1007/bf01885176
|View full text |Cite
|
Sign up to set email alerts
|

Accessory spleen: Presentation as a large abdominal mass in an asymptomatic young woman

Abstract: Accessory spleen hypertrophy is usually related to hematologic, lymphomatous, and rheumatoid diseases. We describe here the case of an 18-year-old asymptomatic woman who presented with a very large accessory spleen occupying the lower abdomen. Its appearance on abdominal sonogram, computed tomogram, and hepatosplenic scintigraphy is correlated with the resected specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…When these patients are examined with sonography, CT, or MR imaging for various reasons, these enlarged ASs may then resemble metastases, neoplasia due to lymphoproliferative disease, or tumors arising from adjacent organs, such as the left kidney, adrenal gland, and pancreas. 2,6,8,10,11,13,26,27 Additionally, the localization of an AS may also lead to difficulties in the differential diagnosis. 25 Although most ASs occur within the left upper part of the abdomen, they may, according to their embryologic contiguity to the genital ridge, occur elsewhere in the abdomen or even within the scrotum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these patients are examined with sonography, CT, or MR imaging for various reasons, these enlarged ASs may then resemble metastases, neoplasia due to lymphoproliferative disease, or tumors arising from adjacent organs, such as the left kidney, adrenal gland, and pancreas. 2,6,8,10,11,13,26,27 Additionally, the localization of an AS may also lead to difficulties in the differential diagnosis. 25 Although most ASs occur within the left upper part of the abdomen, they may, according to their embryologic contiguity to the genital ridge, occur elsewhere in the abdomen or even within the scrotum.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] A hypertrophic accessory spleen (HAS) occurring after splenectomy is one of the differential diagnoses of abdominal masses usually found incidentally in these patients. 1,2,[6][7][8][9][10][11] An accessory spleen (AS) is formed from separated fetal spleen tissue and in general measures a few millimeters in size. It is often missed during splenectomy.…”
mentioning
confidence: 99%
“…Accessory spleens presenting as a large abdominal mass (Mostbeck et al, 1987) or a retroperitoneal tumor (Rosenthal and Bishop, 1981;Miller et al, 1990) have also been reported. An accessory spleen rarely presents as a surgical emergency, with symptoms of "acute abdomen" due to torsion (Kitchin and Green, 1962), infarction (Babcock et al, 1974), rupture (Texeira and Hardin, 1974), and intestinal obstruction (Patruskev, 1970).…”
Section: Clinical Significancementioning
confidence: 93%
“…The notion that regenerated spleens have a functional value is supported by their normal tissue architecture. 1 More importantly, the volume of regenerated splenic tissue seems to correlate with protection against postsplenectomy infection. 10 The existence of functional splenic tissue is indicated by the absence of Howell-Jolly bodies and presence of normal IgM blood levels.…”
Section: Commentmentioning
confidence: 99%
“…Autotransplantation of splenic tissue after traumatic disruption of the splenic capsule is well recognized. 1 Splenic tissue can lodge anywhere in the peritoneal cavity following traumatic disruption and regenerates under favourable conditions. 2 The incidence of splenic regeneration correlates with the severity of splenic injury: 3 patients requiring a splenectomy for trauma tend to be those with greatest splenic damage and dissipation of splenic tissue, which favours autotransplantation.…”
Section: Commentmentioning
confidence: 99%